Real-World Effectiveness and Safety of Selective JAK Inhibitors in Ulcerative Colitis and Crohn’s Disease A Retrospective, Multicentre Study - Farkas Bernadett; Bessissow Talat; Limdi Jimmy K.; Sethi-Arora Karishma; Kagramanova Anna; Knyazev Oleg; Bezzio Cristina; Armuzzi Alessandro; Lukas Milan; Michalopoulos George; Chaskova Elena; Savarino Edoardo Vincenzo; et al. (2024)
Background/Objectives: Data on the real-world effectiveness and safety of selective JAK inhibitors (JAKis) in ulcerative colitis (UC) and Crohn’s disease (CD) are limited. Methods: We conducted a multicentre, retrospective study to assess clinical, biochemical, and endoscopic outcomes of selective JAKis in bio-experienced UC and CD. Results: A total of 246 patients (mean age: 40.5 ± 14.5 years; 131 UC and 115 CD) were included with a median follow-up of 7.5 months. Among the CD patients receiving upadacitinib (n = 115), 76.2% achieved clinical remission (CR) at week 12. Furthermore, 59.5% of the upadacitinib-treated UC patients (n = 100) experienced CR at week 8. Corticosteroid-free CR (CSFCR) was achieved by 76.9% of the CD patients and 80.6% of the UC patients at week 24, while 50.0% and 36.1% experienced endoscopic remission. At week 52, 66.7% of the CD and 86.2% of the UC patients achieved CSFCR, whereas 54.5% and 52.9% had endoscopic remission. In UC, the effectiveness of upadacitinib was not compromised by prior tofacitinib failure, while the upadacitinib-treated CD patients with stricturing and penetrating disease were less likely to achieve CR by the end of the induction phase (p = 0.04). C-reactive protein (p[CD] < 0.0001; p[UC] < 0.0001) and faecal calprotectin (p[CD] < 0.0001; p[UC] = 0.02) decreased significantly in both patient groups as early as week 2. Among the filgotinib-treated UC patients (n = 31), 28.6% were in CR at week 12. At week 24 and 52, 59.1% and 60% achieved CSFCR, while 0.0% and 20.0% had endoscopic remission. Both C-reactive protein (p = 0.04) and faecal calprotectin (p = 0.04) decreased significantly by week 12. Hyperlipidaemia (9.7–9.8%) was the most common adverse event. Conclusions: Selective JAKis are rapidly effective and safe for treating refractory, moderate-to-severe CD and UC.
Keywords: Gasztroenterológia és hepatológia